Pengaruh Konsentrasi Sari Jahe Emprit (Zingiber Officinale Var. Amarum ) Dan Lama Penyimpanan Terhadap Jumlah Mikrobia Pada Susu Sapi - Lathifah, Umi, Eni Purwani,S.Si., M.Si (2017)
Cow's milk contains nutrients such as protein, fat and carbohydrate that are good for growth and development, but makes cow's milk susceptible to damage and causes a relatively short storage time. The pasteurization process can inhibit damage of the cow's milk. Pasteurization temperatures used for this study is 65oC for 30 minutes Gingerol antimicrobial substances contained in ginger may inhibit the growth of microorganisms. The purpose of this study was to determine the effect of ginger extract and storage time on the total microbial and acceptability of milk. This research used experimental method with a completely randomized design. Ginger extract concentration variation were 0%, 1.5%, 2.5% and 3.5%. Variations of storage time were 0 hour, 3 hours, 6 hours and 9 hours. Total of microbes calculated using the TPC. Data analysis uses Kruskal-Wallis and the difference results analysis using Duncan test with a confidence level of 5%. The results showed that the highest total number of microbes was found in concentration of ginger extract 2.5% and 3 hours of storage time (8,2x106 cfu / ml). Based on the Kruskal-Wallis test between the concentration of ginger juice with total microbial obtained value of p = 0.082 (p> 0.05) as well as the total storage time with microbes derived value of p = 0.076 (p> 0.05). In acceptability there were a difference in color, aroma, flavor, viscosity and overall. Overall the most preferred is 1.5% concentration of ginger juice with assessment score of 3.3. Based on these studies obtained the best results is ginger extract concentration of 1.5% with storage time 3 hours with the number of microbes 1,2x105 cfu / ml. Keywords: cow's milk, ginger, pasteurization, storage time, number of microbes